Pulmonary Targeting of Levofloxacin Using Microsphere-Based Dry Powder Inhalation - Turki Al Hagbani; Bhavya Vishwa; Amr S. Abu Lila; Hadil Faris Alotaibi; El-Sayed Khafagy; Afrasim Moin; Devegowda V. Gowda (MDPI AG, 2022)
The objective of the current study was to develop poly (lactic-co-glycolic acid) (PLGA) microspheres loaded with the anti-tuberculosis (anti-TB) fluoroquinolone, Levofloxacin (LVX), in the form of dry powder inhalation (DPI). LVX-loaded microspheres were fabricated by solvent evaporation technique. Central Composite Design (CCD) was adopted to optimize the microspheres, with desired particle size, drug loading, and drug entrapment efficiency, for targeting alveolar macrophages via non-invasive pulmonary delivery. Structural characterization studies by differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction analysis revealed the absence of any possible chemical interaction between the drug and the polymer used for the preparation of microspheres. In addition, the optimized drug-loaded microspheres exhibited desired average aerodynamic diameter of 2.13 ± 1.24 μm and fine particle fraction of 75.35 ± 1.42%, indicating good aerosolization properties. In vivo data demonstrated that LVX-loaded microspheres had superior lung accumulation, as evident by a two-fold increase in the area under the curve AUC0-24h, as compared with plain LVX. Furthermore, LVX-loaded microspheres prolonged drug residence time in the lung and maintained a relatively high drug concentration for a longer time, which contributed to a reduced leakage in the systemic circulation. In conclusion, inhalable LVX-loaded microspheres might represent a plausible delivery vehicle for targeting pulmonary tuberculosis via enhancing the therapeutic efficacy of LVX while minimizing its systemic off-target side effects.